DETERMINANTS OF ALLOCATIVE EFFICIENCY OF RAIN-FED RICE PRODUCTION IN TARABA STATE, NIGERIA - Tijjani, A.; Bakari, U.M (European Scientific Journal, ESJ, 2014)
This paper analyzed the determinants of allocative efficiency of rainfed rice production in Taraba State, Nigeria. Structured questionnaire was used to collect data from 234 rain-fed rice farmers through multi-stage random sampling. Stochastic frontier cost function was employed to analyse the data. Majority (82%) of the respondents were males, 84% of them were in their active ages (21-50 years), 89% had one form of formal education or the other, 64% have farmed for more than five years and about 85% were small scale holders. The diagnostic statistics, gamma (0.84) and sigma squared (0.03), were statistically significant at 1% probability level. The result further revealed that cost of herbicide, seed and family labour were significant at 1% level, while cost of hired labour and ploughing were significant at 5% level. The mean allocative efficiency (AE) was 0.69.. The analysis also showed that education and farming experience were the major determinants of allocative efficiency among the respondents. Government should enhance farmers’ education levels through the establishment of functional literacy classes to improve their allocative efficiency.